2000
DOI: 10.1103/physrevb.61.3219
|View full text |Cite
|
Sign up to set email alerts
|

Thermoremanence anomaly in Fe-Zr(B,Cu) Invar metallic glasses: Volume expansion induced ferromagnetism

Abstract: We report the existence of a thermally induced sharp increase of thermoremanence around the Curie temperature of Invar-like Fe-Zr͑B,Cu͒ soft magnetic glasses. Neutron-diffraction measurements indicate that a true enhancement of the average local magnetic moment, rather than only a change in the domain structure, occurs. Such enhancement has been tentatively attributed to the increasing volume expansion that takes place beyond the Curie temperature and reinforces ferromagnetism in some low-density clusters.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Strong magnetovolume effects, such high volume magnetostriction pressure effects on magnetization, and Curie temperature as well as invar and anti-invar behavior have been reported not only in Fe alloys with FCC structure, such as FeNi, 4 FePt, 5 FeCu, [6][7][8] but also in Fe based amorphous alloys. 9,10 Such effects are likely caused by the dependence of the band width on the atomic distances, in consequence the magnetic structure changes upon modification of the lattice dimensions.…”
mentioning
confidence: 99%
“…Strong magnetovolume effects, such high volume magnetostriction pressure effects on magnetization, and Curie temperature as well as invar and anti-invar behavior have been reported not only in Fe alloys with FCC structure, such as FeNi, 4 FePt, 5 FeCu, [6][7][8] but also in Fe based amorphous alloys. 9,10 Such effects are likely caused by the dependence of the band width on the atomic distances, in consequence the magnetic structure changes upon modification of the lattice dimensions.…”
mentioning
confidence: 99%
“…12,13 It was shown that the TRM values spontaneously increased above Curie temperature. Such enhancement in TRM values could not be due to structural changes and was tentatively attributed to thermal-expansion effects.…”
mentioning
confidence: 99%